ФИЗИЧЕСКОЕ РАЗВИТИЕ ДЕТЕЙ В ПЕРИОД НАЧАЛЬНОГО ШКОЛЬНОГО ОБРАЗОВАНИЯ - Утепбергенов, А.К.; Мамутов, П.Ж. (SCIENCE and SOCIETY, 2025)
The physical development of children during the primary school period is a crucial component of the child's overall development, influencing their health, psycho-emotional state, and academic success. The article discusses the characteristics of children's physical development, the impact of school workloads and physical exercises on the child's body, as well as the role of teachers and parents in ensuring harmonious development.
Keywords: physical development; primary school education; children; health; physical education; pedagogical activity; school workload